Silicon application affects cadmium translocation and physiological traits of Lallemantia royleana under cadmium stress. (15th March 2020) - Rostami, Majid; Mohammadi, Hoda; Müller, Torsten; Mirzaeitalarposhti, Reza
Abstract: To study the interaction of different concentrations of cadmium and silicon on physiological traits of Lallemantia royleana a factorial experiment was conducted based on a completely randomized design. Experimental treatments were different concentrations of cadmium (0, 2.5, 5 and 10 mg L −1 ) in the absence (-Si) or presence (+Si) of silicon with a concentration of 1 mmol L −1 . Based on results the highest amount of shoot Cd content (84.1 mg kg −1 DW) measured in -Si treatments was measured when the highest concentration of Cd (10 mg Cd L −1 ) was utilized. In all of the + Si treatments shoot Cd content decreased. The highest translocation factor (0.195) was observed in 2.5 mg Cd L −1 treatment without Si application and as a result of increasing Cd concentration in plant growth medium, the translocation factor decreased significantly. In + Si treated plants the translocation factor of Cd compared with –Si treated plants significantly decreased. Increasing the cadmium concentration up to 2.5 mg.L −1 did not have a significant effect on relative water content, leaf area, Chlorophyll a, and catalase activity. At the highest concentration of cadmium, the activity of peroxidase, catalase and superoxide dismutase in + Si plants compared with -Si plants increased about 23%, 55% and 30%, respectively. Silicon reduced the negative effects of cadmium on plant growth either by increasing the activity of antioxidant enzymes or decreasing Cd translocation to shoot. Therefore, application of silicon for increasing growth and to produce healthier plants under cadmium stress with a concentration of 5 mg L −1 is recommended.